Nature's Calendar: Plant's Calendar - phenological observations made by Citizen Scientists - Langvall, Ola; Dahl, Åslög; Johansson, Jacob; Bolmgren, Kjell (Swedish University of Agricultural Sciences, 2025)
Nature's Calendar (www.naturenskalender.se, in Swedish only) is run by the Swedish National Phenology Network (SWE-NPN), a consortium of Swedish universities, governmental agencies and non-governmental organisations. The Swedish University of Agricultural Sciences (SLU) hosts the network and is part of the Climate program within the environmental monitoring and assessment activity branch of the university. The main task for the Nature's calendar is to collect observations of different spring and autumn signs appearing during the vegetation season. SWE-NPN is connected to the monitoring of the Swedish Environmental Objectives, mainly concerning the objective Reduced Climate Impact, but is also collaborating with networks in Europe (through the Pan-European Phenology database - PEP725) and internationally (through the International Society of Biometeorology).

Data about the nature's calendar is collected in two ways, the long-term environmental monitoring through "Calendars", where phenological observations are reported all through the year, and through "Checks", where phenology observations are reported during short-time campaigns, giving a snapshot of the phenological status at a certain time of the year. The long-term environmental monitoring is performed by citizen scientists and professional observers at research stations and like. Three calendars have been launched in the Nature's Calendar; the Plant's Calendar (from 2008), the Bird's Calendar (from 2016) and the Beekeeper's Calendar (between 2015 and 2018).

Aims
The aim of the Nature's Calendar is to collect phenological data from the first spring sign to the last autumn sign, to be able to offer nation-wide data to everyone interested, to facilitate research, environmental assessments, the evaluation of environmental goals, etc, to be better prepared to meet the effects of climate change. Observations reported to the Nature's Calendar can be compared to similar observations collected for more than 100 years ago (see the Swedish Historical Phenology Dataset in "Related Reseach Data"), to detect evidence of phenological shifts over time that can be connected to climate change. Data from this dataset is used e.g. for the the evaluation of the Swedish Environmental Objectives, by producing the indicators "Growing season" and "Spring signs" (www.slu.se/vaxternasvaxtsasong).

In the Plant's Calendar, Citizen Scientist's have reported observations of how
- budburst and leaf development (broadleaves)
- budburst and shoot elongation (conifers)
- flowering
- ripening of fruits and berries
- seed dispersal
- autumn colors
- leaf shedding
develop during the growing season.

The dataset includes one file with observation data (plants_calendar_2008-2024.csv), one file with the species list used by the observers (in total 1252 species, see plants_calendar_specieslist_2008-2024.csv) and one file with the full list of phenological phases and sub-phases that observers can report (in total 38 phases, see plants_calendar_phaselist_2008-2024.csv). Furthermore, three documents are available, one PDF file (metadata_plants_calendar_2008-2024.pdf) with metadata that describes how the above mentioned CSV files are related and how the included parameters should be interpreted, one PDF file (vaxtkalendern_fenologimanual_2021.pdf) which describes the protocol used by those included in the phenology observer programme, i.e. the observations indicated as high quality (in Swedish, only), and one file with the list of nationally protected species according to the Swedish Species Information Centre (lista-nationellt-skyddsklassade-arter-20230612-uppdat-20240425.pdf, in Swedish only). The observation data file includes totally 166 396 observations.

The data collection in the "Nature's Calendar - Plant's Calendar" started in 2008, but some observations made at a few locations at earlier dates have also been registered in the database, so this dataset includes a few records already from 1980 and forward.

Coordinates of a few observation locations have been made diffuse, to make tracing back to the original location impossible (coordinates are rounded to 1.5 decimals = > 6 km diffusion), concerning protected species, as to the rules for publicly handling of nationally protected species (see https://www.artdatabanken.se/var-verksamhet/fynddata/skyddsklassade-arter/).

Naturens kalender (www.naturenskalender.se) drivs av Svenska fenologinätverket, som är ett nätverk med flera universitet, myndigheter och föreningar. Sveriges lantbruksuniversitet (SLU) är nätverkets huvudman och ingår i universitetets miljöanalysverksamhet, tillhörande delprogrammet Klimat. Huvuduppgiften för Naturens kalender är att samla in observationer av vårtecken, hösttecken och annat i naturens kalender. Nätverkets verksamhet är i första hand kopplat till Sveriges miljökvalitetsmål Begränsad klimatpåverkan, men ingår även i europeiska (genom Pan-European Phenology database - PEP725) och intermationella (genom International Society of Biometeorology) samarbeten kring fenologisk forskning och miljöövervakning.

Data om naturens kalender samlas in på två olika sätt. Dels bedrivs en långsiktig miljöövervakning i form av ”kalendrar” där rapporter om fenologiska observationer samlas in över hela året, dels genomför vi korta ”kollar” där vi tar en ögonblicksbild av naturens kalender i landet vid en viss tidpunkt på året. Den långsiktiga miljöövervakningen genomförs av frivilliga och professionella medborgarforskare, s.k. fenologiväktare, i Växtkalendern (från 2008), Fågelkalendern (från 2016) och Bikalendern (2015-2018).

Motiv och syfte
Målet med Naturens kalender är att samla in data om allt från första vårtecken till sista hösttecken, så att vi kan erbjuda landsomfattande data till alla intresserade, för att underlätta forskning, miljömålsarbete och information, vilket kan göra oss bättre rustade att möta klimatförändringens effekter. Observationerna i Naturens kalender kan jämföras med motsvarande observationer som gjordes för över 100 år sedan (se Svenskt historiskt fenologidataset i "Relaterade forskningsdata"), för att upptäcka fenologiska förändringar över tid som kan bero på klimatförändringar. Data från Växtkalendern används exempelvis till uppföljningen av de svenska miljömålen genom miljömålsindikatorerna ”Växternas växtsäsong” och "Vårtecken" (www.slu.se/vaxternasvaxtsasong).

I Växtkalendern har medborgarforskare rapporterat in observationer av hur
- blomning
- lövsprickning
- barrträds skottskjutning
- bär- och fruktmognad
- fröspridning
- höstlövens färger
- lövfällning
utvecklas under växtsäsongen.

Datasetet innehåller en fil med observationsdata (plants_calendar_2008-2024.csv), en fil med artlistan som använts av observatörerna i rapporteringarna som ingår i detta dataset (totalt 1252 arter, se plants_calendar_specieslist_2008-2024.csv) och en fil med kompletta listan över de fenologiska faser som observatörerna kan rapportera (totalt 38 faser, se plants_calendar_phaselist_2008-2024.csv). Dessutom finns det tre dokument, dels en PDF-fil (metadata_plants_calendar_2008-2024.pdf) med metadata som beskriver hur ovanstående filer relaterar varandra samt beskriver ingående variabler, samt en PDF-fil (vaxtkalendern_fenologimanual_2021.pdf), som är den manual som s.k. fenologiväktare lovat följa (d.v.s. de som rapporterar med en högre kvalitet), och slutligen ett dokument med den nationella artskyddslistan (lista-nationellt-skyddsklassade-arter-20230612-uppdat-20240425.pdf). Observationsdatafilen innehåller totalt 166 396 observationer.

Observationsdatafilen kan användas fristående, övriga filer kan ses som kompletterande information för att förstå innehållet i denna (liksom att få fenologiska faserna i engelsk översättning).

Datainsamlingen i "Naturens kalender - Växtkalendern" påbörjades 2008, men ett antal observationer från enskilda observationsplatser som gjorts vid tidigare datum har också registrerats i databasen, varför observationsdatafilen innehåller enstaka observationer ända från 1980 t.o.m. 2024.

Koordinaterna för ett fåtal observationsplatser har gjorts diffusa, gällande observationer av skyddsvärda arter (avrundning till 1,5 decimaler = >6 km diffusion) i enlighet med reglerna för publik hantering av nationellt skyddade arter (se https://www.artdatabanken.se/var-verksamhet/fynddata/skyddsklassade-arter/).
Naturens kalender: Växtkalendern - fenologiska observationer av medborgarforskare
Keywords: PLANT PHENOLOGY; Species distribution; Arters utbredning; phenology; participatory research; deltagande forskning; citizen science; citizen science; medborgarforskning; Nature's calendar; Naturens kalender; phenology; fenologi; Climate Science; Klimatvetenskap; Environmental Sciences; Miljövetenskap; Ecology; Ekologi; Biota; Biologi och ekologi